CLASSIC MODEL OF TRANSITION PERIOD (Scientific journal of the Fergana State University, 2023)
The article analyzes priority branches of transition period using the foreign experience through the scientific-practical bases.The socio-political and spiritual condition, features and conditions of each stage of transition period have also been enlightened.